Determinansi Tingkat Pengalaman Mengajar dan Tingkat Pendidikan Terhadap Kinerja Dosen - Adnan Dini; Heri Sutanto; Muhammad Saleh (Movere Journal, 2023)
Abstract: This study aims to determine the determinants of the level of teaching experience and level of education on lecturer performance. This research was carried out within the scope of the Makassar Barombong Shipping Polytechnic. The design of this research is to use a descriptive research type and the method used in this research is a survey method with path analysis techniques for data analysis. At the Makassar Barombong Shipping Polytechnic, the total study population was 85 lecturers. So in total there are 85 lecturers. The hypotheses put forward in this study are all acceptable because each effect shown has a P-Values ​​<0.05. So it can be stated that the independent variable to the dependent has a significant influence.